A Review on Parameters of Internet Gateway Discovery in MANETS - Osman, Husna; Ebedon, Mufind Mukaz; Saad, Amna (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Mobile ad hoc Networks researchers need to apply specific parameters in the simulation tools chosen to analyze and discuss their results. The challenge faced by multiple authors is on how to decide on the choice of particular parameters. A wrong choice could lead to a no credible result and a doubtful result by other researchers. A best practice is to follow what other authors are using as input parameters in their paper. This review analyses 72 proceeding papers and articles in different digital libraries: google scholar, IEEE Xplore, Elsevier, Springer, and snowball from 2010-2020. We present the result of our survey in this paper. We recommend the input parameters research should use base on the high utilization. Our review will also help the community in MANET and Internet gateway to improve the credibility of the input parameters.